PELAKSANAAN PENGAWASAN DINAS KESEHATAN KABUPATEN KAMPAR BERDASARKAN PERATURAN BUPATI NOMOR 42 TAHUN 2016 TERHADAP PELAYANAN KESEHATAN RUMAH SAKIT UMUM DAERAH BANGKINANG - Fitri, Dewinta; Indra, Mexsasai; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Supervision is the process of examining the implementation of an activity that has been previously planned. Supervision of health services at the Bangkinang Hospital is one of the responsibilities of the Kampar District Health Office. In the periodic supervision carried out by the Kampar District Health Office on the Bangkinang Hospital, it is hoped that it can produce results by increasing health services from the Bangkinang Hospital. In this paper the authors focus on monitoring conducted by the Department of Health carried out as for the purpose of writing this paper: First, to find out the oversight conducted by the Health Service Ka Kampar district to Bangkinang Hospital. Second , to find out the inhibiting factors in the supervision process. Third , to find out the efforts made to overcome obstacles in the supervision process.Research conducted by the author, found the results that supervision has been carried out. However, there are still obstacles, one of which is the high expectation of getting excellent health services. So that the Health Office seeks to improve services by increasing the type of Bangkinang Hospital.The author's suggestion is to increase the accuracy of the Health Office in carrying out supervision following up on complaints from the community.Keywords: Department of helth- Hospital Bangkinang - Supervision - Health services.